P-D1 Transient stimulation of cells harboring latent proviruses contributes to the methylation of the HIV-1 promoter. (March 2017) - Trejbalova, Katerina; Kovarova, Denisa; Blazkova, Jana; Machala, Ladislav; Jilich, David; Weber, Jan; Kucerova, Dana; Vencalek, Ondrej; Hirsch, Ivan; Hejnar, Jiri
Abstract : Human immunodeficiency virus type 1 (HIV-1) latency represents the major barrier to virus eradication in infected individuals because cells harboring latent HIV-1 provirus are not affected by current antiretroviral therapy (ART). We previously demonstrated that DNA methylation of HIV-1 long terminal repeat (5′ LTR) restricts HIV-1 reactivation and, together with chromatin conformation, represents an important mechanism of HIV-1 latency maintenance. Here, we explored the new issue of temporal development of DNA methylation in latent HIV-1 5′ LTR. In the Jurkat CD4(+) T cell model of latency, we showed that the stimulation of host cells contributed to de novo DNA methylation of the latent HIV-1 5′ LTR sequences. Consecutive stimulations of model CD4(+) T cell line with TNF-α and PMA or with SAHA contributed to the progressive accumulation of 5′ LTR DNA methylation. Further, we showed that once established, the high DNA methylation level of the latent 5′ LTR in the cell line model was a stable epigenetic mark. Finally, we explored the development of 5′ LTR DNA methylation in the latent reservoir of HIV-1- infected individuals who were treated with ART. We detected low levels of 5′ LTR DNA methylation in the resting CD4(+) T cells of the group of patients who were treated for up to 3 years. However, after long-term ART, we observed an accumulation of 5′ LTR DNA methylation in the latent reservoir. Importantly, within the latent reservoir of some long-term- treated individuals, we uncovered populations of proviral molecules with a high density of 5′ LTR CpG methylation. Our data showed the presence of 5′ LTR DNA methylation in the long-term reservoir of HIV-1-infected individuals and implied that the transient stimulation of cells harboring latent proviruses may contribute, at least in part, to the methylation of the HIV-1 promoter.